Approximation method for the sewer drainage effect for urban flood modeling in areas without drainage-pipe data - Li, Donglai; Hou, Jingming; Shen, Ruozhu; Li, Bingyao; Tong, Yu; Wang, Tian (Frontiers in Environmental Science, 2023)
The underground drainage-pipe network is one of the vital components of modern city, which plays an important role in preventing or mitigating urban flood. Thus, pipe network data is necessary to the whole process of urban rainfall runoff simulation. However, pipe network data are sparse or unavailable in most urban areas. To solve this problem, this paper developed a novel approximation method which can calculate the drainage capacity of pipe system. The method was named as the road-drainage method, and it assumed that the pipe worked by subtracting corresponding mass from water conservation equation only from the road area. The mass is determined from weir flow formulas together with the road properties, then gets corrected in the rainfall source term. Two test cases were used to compare the performance of the new method with existing method which subtracts mass from the whole area during rainfall runoff process. Results show that the new method considerably improves the simulation accuracy of peak volume by 2.62 % - 58.75 % compared with the existing method in different scenarios. Moreover, the proposed new method reduces the shift time by 10 - 45 min at the rising and peak of surface inundation for different scenarios, which reflects a more realistic rainfall-runoff process. These results demonstrate that the proposed new method can represent the drainage capability more accurately and more consistent with the reality. The road-drainage method has promising potential to be applied in urban flood simulation in the area without drainage system data and support large-scale urban hydrologic modeling.